The genome of the jellyfish Aurelia and the evolution of animal complexity. Issue 1 (January 2019) - Gold, David; Katsuki, Takeo; Li, Yang; Yan, Xifeng; Regulski, Michael; Ibberson, David; Holstein, Thomas; Steele, Robert; Jacobs, David; Greenspan, Ralph
Abstract We present the genome of the moon jellyfishAurelia, a genome from a cnidarian with a medusa life stage. Our analyses suggest that gene gain and loss inAurelia is comparable to what has been found in its morphologically simpler relatives—the anthozoan corals and sea anemones. RNA sequencing analysis does not support the hypothesis that taxonomically restricted (orphan) genes play an oversized role in the development of the medusa stage. Instead, genes broadly conserved across animals and eukaryotes play comparable roles throughout the life cycle. All life stages ofAurelia are significantly enriched in the expression of genes that are hypothesized to interact in protein networks found in bilaterian animals. Collectively, our results suggest that increased life cycle complexity inAurelia does not correlate with an increased number of genes. This leads to two possible evolutionary scenarios: either medusozoans evolved their complex medusa life stage (with concomitant shifts into new ecological niches) primarily by re-working genetic pathways already present in the last common ancestor of cnidarians, or the earliest cnidarians had a medusa life stage, which was subsequently lost in the anthozoans. While we favour the earlier hypothesis, the latter is consistent with growing evidence that many of the earliest animals were more physically complex than previously hypothesized. The cnidarian moon jellyfishAurelia has a medusa life stage with a complex neural system. By comparing theAurelia genome and transcriptomes from different life stages with those of other cnidarians, the authors show that life cycle complexity is not associated with increased number of genes.